2015
DOI: 10.3390/rs70403548
|View full text |Cite
|
Sign up to set email alerts
|

Sea Surface Wind Retrievals from SIR-C/X-SAR Data: A Revisit

Abstract: Abstract:The Geophysical Model Function (GMF) XMOD1 provides a linear algorithm for sea surface wind field retrievals for the Spaceborne Imaging Radar-C/X-band Synthetic Aperture Radar (SIR-C/X-SAR). However, the relationship between the normalized radar cross section (NRCS) and the sea surface wind speed, wind direction and incidence angles is non-linear. Therefore, in this paper, XMOD1 is revisited using the full dataset of X-SAR acquired over the ocean. We analyze the detailed relationship between the X-SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Typically, wind information over the sea surface is provided by ancillary in situ and/or remotely-sensed data, e.g., buoy measurements and/or scatterometer and radiometer satellite data. The former measure sea surface wind speed at the usual height of 5 m, while the latter allow retrieving near surface wind speed at a reference height of 10 m above sea level [43][44][45]. Unfortunately, very often, the information coming from other remotely-sensed sources is not colocated in time and/or space with the available SAR dataset.…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…Typically, wind information over the sea surface is provided by ancillary in situ and/or remotely-sensed data, e.g., buoy measurements and/or scatterometer and radiometer satellite data. The former measure sea surface wind speed at the usual height of 5 m, while the latter allow retrieving near surface wind speed at a reference height of 10 m above sea level [43][44][45]. Unfortunately, very often, the information coming from other remotely-sensed sources is not colocated in time and/or space with the available SAR dataset.…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…Although several algorithms have been recently exploited for wind retrieval from co-polarization TS-X/TD-X image, such as GMF SIRX-MOD [3], GMF XMOD2 [4] and polarization ratio XPRs [2,5], these algorithms are only valid for wind speeds up to 25 m/s. When XWAVE is applied for wave retrieval from HH-polarization TS-X/TD-X image, XPR has to be used for converting NRCS in HH-polarization to NRCS in VV-polarization to retrieve wind speed.…”
Section: Discussionmentioning
confidence: 99%
“…Then, similar to the development of C-band GMF CMOD5 [33] that was derived from ERS-1 SAR images and ECMWF reanalysis wind data, XMOD2 has been exploited in [4] by using collocated VV-polarization TS-X/TD-X images and National Data Buoy Center (NDBC) buoy measurements and it was found that a 1.44 m/s RMSE of wind speed was achieved against NOAA in situ buoys. Besides, another X-band GMF, called SIRX-MOD, was proposed in [3] by retuning the coefficients in the C-band GMF CMOD-IFR2 [34] with the VVpolarization Spaceborne Imaging Radar (SIR) X-band SAR NRCS data and ECMWF reanalysis wind data. XMOD2 and SIRX-MOD take the general form of:…”
Section: Existing X-band Sar Wind and Wave Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The correcting term is a function of wavenumber and wind speed with twelve adjusted parameters, which are derived from L-, C-and Ku-band radar backscatter. It is noted that the X-band GMF has been developed by Li et al [29] and Ren et al [30]. But the upwind-crosswind asymmetry in their GMFs needs to be verified by large amounts of data.…”
Section: Discussionmentioning
confidence: 99%